The treatment of a Morel-Lavallée lesion of the thigh with incision and drainage along with tissue debridement and a surgically placed drain: A case report and literature review - Hu, Minhua; Chen, Junbang; Ma, Luyao; Huang, Feng; Cai, Qunbin (Frontiers in Surgery, 2023)
Background A Morel-Lavallée lesion (MLL) is a rare closed degloving injury that usually occurs around the hips and is associated with pelvic fractures after high-energy trauma, which is commonly overshadowed by other severe post-traumatic manifestations. An isolated MLL, mostly caused by low-energy violence, is even rarer. Thus, the rates of misdiagnosis and missed diagnosis are often high. In this case report and literature review, we review the pathophysiology, clinical manifestations, imaging data, and treatment of this lesion to increase awareness of this rare disease. Case report We report the case of an isolated MLL in the right thigh caused by trauma, which happened to be one of missed diagnosis both at the initial visit and at the return visit of the patient, with a significant sign of a mass on MRI. Given the size of the lesion, open debridement and irrigation were adopted to treat the lesion, and the patient recovered well post-operatively. Conclusion Young surgeons should pay attention to the MLL with sufficient recognization to avoid missed diagnosis and misdiagnosis. Comprehensive physical examination and imaging data play important roles in the diagnosis of MLL. In the early stages of this injury, a detailed history review combined with physical examination and MRI, can reduce the rates of missed diagnosis and misdiagnosis. The choice of the therapeutic scheme depends on the size and severity of the lesion. For an isolated MLL, compared with conservative treatments, we suggest that incision and drainage, along with tissue debridement and a surgically placed drain, will reduce the rates of infection and recurrence.